Lycium mellitum J. Z. Dong, A new species of Solanaceae Juss. from Qinghai, China (Bangladesh Journal of Plant Taxonomy, 2025)
The new species Lycium mellitum J. Z. Dong (Solanaceae) is established and illustrated from Qinghai province of China. It has a close association with L. ruthenicum and L. ostrum J.Z. Dong, but is distinguished by several morphological characters: stems much branched, thorns at nodes or not, usually clustered with leaves and flowers; leaves narrowly linear, fleshy, gray, usually apically light yellow; pedicel 10-20 mm long; berries orange-yellow, nearly transparent, inside placenta faintly visible; seeds 1-5, rarely more, light brown.Bangladesh J. Plant Taxon. 32(1): 123-127, 2025 (June)